The Effect of Variation in Cabopol Concentration on Peel-off Gel Mask from Avocado (Persea americana Mill.) Fruit Extract - Nakii, Siti Fatmawaty; Thomas, Nurain; Latif, Multiani S. (Jurnal Literasi Mandiri, 2025)
Avocado (Persea americana Mill.) is a natural ingredient commonly used in the formulation of peel-off gel masks due to its content of vitamins, minerals, proteins, fiber, and antioxidant compounds such as flavonoids. This study aimed to investigate the effect of varying carbopol concentrations on the physical properties of peel-off gel masks containing avocado fruit extract. The methods included avocado fruit extraction using maceration, formulation of peel-off gel masks with varying carbopol concentrations (0.5%, 1%, and 2%), and physical evaluation of the preparations, including organoleptic testing, pH, homogeneity, viscosity, spreadability, adhesion, and drying time. The results showed that all formulations had good physical stability, including organoleptic testing, homogeneity, pH, and viscosity. Increasing the carbopol concentration resulted in higher viscosity and thicker gel. Additionally, spreadability and adhesion also showed good results, while the drying time increased with higher carbopol concentrations. Based on these findings, it can be concluded that varying carbopol concentrations influence the physical properties of the peel-off gel mask with good stability and effectiveness as a cosmetic product.